Bilinguals’ Sensitivity to Grammatical Gender Cues in Russian: The Role of Cumulative Input, Proficiency, and Dominance - Mitrofanova, Natalia; Rodina, Yulia; Urek, Olga; Westergaard, Marit (Frontiers in Psychology, 2018)
This paper reports on an experimental study investigating the acquisition of grammatical gender in Russian by heritage speakers living in Norway. The participants are 54 Norwegian-Russian bilingual children (4;0-10;2) as well as 107 Russian monolingual controls (3;0-7;0). Previous research has shown that grammatical gender is problematic for bilingual speakers, especially in cases where gender assignment is opaque (Schwartz et al., 2015; Polinsky, 2008; Rodina and Westergaard, 2017). Furthermore, factors such as proficiency and family type (one or two Russian-speaking parents) have been argued to be important. Interestingly, previous findings differ with respect to the kind of errors children make: restructuring to a two-gender system (masculine-feminine, see Polinsky, 2008) or defaulting to masculine (see Rodina and Westergaard, 2017). It is also not clear to what extent children are sensitive to gender cues or whether certain agreement patterns are simply memorized. To investigate this, we used both existing nouns and nonce words and tested both transparent and opaque gender cues. The results were checked against a number of background factors measuring exposure, proficiency, and dominance. Our findings show that bilingual children are clearly sensitive to morphophonological cues for gender assignment. The most common and robust error pattern for all bilinguals involved overgeneralization to masculine (especially affecting neuter and opaque nouns). At the same time, children from families with two Russian-speaking parents and monolinguals also occasionally overused feminine with vowel-final nouns. The following variables were found to be the most reliable predictors of accuracy on grammatical gender tasks: cumulative length of exposure (CLoE) and consistency of input in Russian, as well as the presence of older siblings, with CLoE to Russian being by far the most robust and important predictor. Furthermore, we show that a lexical diversity measure (number of different words in a Russian narrative) is also correlated significantly with the children’s performance on the gender tasks. At the same time, our results indicate that relative measures of dominance (e.g., the difference in exposure between the two languages or the difference in narrative scores) may be redundant when more robust absolute measures are present (CLoE and lexical diversity in the heritage language).